2023
DOI: 10.1186/s12885-023-10508-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and verification of a novel circadian clock related long non-coding RNA model and prediction of treatment for survival prognosis in patients with hepatocellular carcinoma

Abstract: Circadian clock genes are significant in the occurrence and development of HCC and long-non coding RNAs (lncRNAs) are closely related to HCC progression. In this study, we aimed to establish a prognostic risk model for HCC. Circadian clock-related lncRNAs expressed in HCC were extracted from The Cancer Genome Atlas. A nomogram was established to predict individual survival rate. Biological processes enriched for risk model transcripts were investigated by Gene Set Enrichment Analysis. Further, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…[32] In addition, Zhang et al identified MKLN1-AS as an important component of HCC prognostic models. [33] All these findings, which are in line with the results of our bioinformatics analyses, indicate that MKLN1-AS could serve as a potential marker for diagnosis and prognosis, as well as a therapeutic target in HCC patients. The Wei et.al find that the inhibition of lncRNA AL590705.3 expression decreased the proliferative capacity of HCC cells but enhanced FDX1 expression.…”
Section: Discussionsupporting
confidence: 85%
“…[32] In addition, Zhang et al identified MKLN1-AS as an important component of HCC prognostic models. [33] All these findings, which are in line with the results of our bioinformatics analyses, indicate that MKLN1-AS could serve as a potential marker for diagnosis and prognosis, as well as a therapeutic target in HCC patients. The Wei et.al find that the inhibition of lncRNA AL590705.3 expression decreased the proliferative capacity of HCC cells but enhanced FDX1 expression.…”
Section: Discussionsupporting
confidence: 85%
“…The reduced levels of lncRNA LINC00987 in LUAD predict poor prognosis and decreased immunotherapy response [ 32 ]. Emerging evidence has suggested that POLH-AS1 can be used as a prognostic and survival marker in patients with hepatocellular carcinoma [ 33 , 34 ]. SVIL-AS1 suppressed chemoresistance by sponging miR-103a while increasing the levels of ICE1, and it could be the possible anti-LUAD chemotherapeutic target [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…LINC01224 has been proved by multiple bioinformatics studies to have great potential as a biomarker of HCC prognosis and immune response and is related to pyroptosis and ferroptosis. [62][63][64][65][66][67] CTD-2510F5.4 was identified as a potential prognostic biomarker in the bioinformatics study of lung adenocarcinoma, gastric cancer, and HCC and is related to ferroptosis in HCC. [67][68][69][70][71][72] RP1-228H13.5 has been revealed to be related to necroptosis, autophagy, pyroptosis, ferroptosis, glycolysis, and other mechanisms of HCC, and has been identified as a prognostic marker of HCC by many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression Related to pyroptosis and ferroptosis [62][63][64][65][66][67] CTD-2510F5. 4 Overexpression Related to ferroptosis [67][68][69][70][71][72] RP1-228H13.…”
Section: Linc01224mentioning
confidence: 99%